Improving Teacher Performance through Self-Efficacy, Training, and Organizational Culture that Enhances Job Satisfaction - Rosalina, Febi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This research aims to determine the influence of self-efficacy, training, and organizational culture on job satisfaction that impacts teacher performance in Vocational High Schools (SMKN) in West Jakarta. The method employed is quantitative. The population of this study comprises all SMKN teachers totaling 432 technical teachers. Sample selection was done using the Slovin formula, resulting in 208 respondents. Data analysis involves validity testing, reliability testing, classic assumption testing, regression analysis, coefficient of determination analysis, and hypothesis testing. The results of this research indicate that self-efficacy has a positive and significant effect on job satisfaction. Training has a positive and significant effect on job satisfaction. Organizational culture has a significant effect on job satisfaction. Self-efficacy, training, and organizational culture simultaneously have a significant impact on job satisfaction. Job satisfaction significantly influences teacher performance.